Experimental and Numerical Analysis of Punching Shear of GFRP-RC Slabs - Al-Ateyat, Aroob; Barakat, Samer; Junaid, M. Talha; Altoubat, Salah; Maalej, Mohamed; Awad, Raghad (Civil Engineering Journal, 2024)
This study investigates the punching shear behavior of Glass Fiber-Reinforced Polymer (GFRP)-reinforced concrete slabs, addressing critical gaps in current design guidelines for high-strength concrete (HSC). The objective is to evaluate the impact of concrete strength, including normal-strength concrete (NSC, 30 MPa) and HSC (60 and 90 MPa), on the punching shear resistance, bridging the lack of experimental data that limits the use of HSC in FRP-reinforced slabs. The research employs experimental testing on three full-scale slab specimens (1.5 m × 1.5 m × 0.1 m) under concentric monotonic loading until failure, coupled with Finite Element Analysis (FEA) using the Concrete Damage Plasticity (CDP) model in ABAQUS. Key findings reveal that increasing concrete strength moderately enhances punching shear resistance by 5.6% and 8.9% for 100% and 200% strength increases, respectively. The FEA model successfully replicates load-deflection behavior, crack patterns, and failure mechanisms with less than a 3% deviation from experimental results. This study enriches the literature with experimental data on GFRP-reinforced slabs using HSC and verifies FEA as a robust design tool for engineers. The findings contribute to developing comprehensive design guidelines for FRP-reinforced slabs subjected to punching shear in high-strength applications. Doi: 10.28991/CEJ-SP2024-010-017 Full Text: PDF